Hubungan Sikap Ergonomi dengan Musculosceletal Disorder Mahasiswa Profesi Ners Universitas Jenderal Soedirman - Candrika Zahra Adelysa; Eva Rahayu; Asep Iskandar (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Background. Musculoskeletal disorders are complaints involving the muscular and skeletal system caused by occupational factors, commonly experienced by nurses and nursing students. Ergonomic attitutudes refers to proper and correct body posture in accordance with ergonomic principles. Suboptimal application of ergonomic attitudes may increase the body’s biomechanical load, thereby causing musculoskeletal complaints. This study aims to examine the relationship between ergonomic attitudes and musculoskeletal disorders among nursing students at Jenderal Soedirman University. Methods. This study used a quantitative correlational design with cross-sectional research design. The sample consisted of 38 respondents selected using a total sampling technique. Data analysis was conducted using Somer’s D test. n observational study with cross sectional approach was conducted. Results. The median age of respondents was 22 years, almost all respondents were female (94,7%), and the majority had a normal body mass (63,2%). The analysis showed the most respondents had good ergonomic attitude (52,7%) and low levels of musculoskeletal disorders complaints (57,9%). The results of Somer’s D test analysis obtained a p-value = 0,003 and correlation coefficient (r) = 0,420. Conclusion. There is a significant relationship with a moderate correlation between ergonomic attitude and complaints of musculoskeletal disorders among nursing profession students at Jenderal Soedirman University. These findings highlight the importance of implementing and habituating ergonomic attitudes early in professional education to minimize musculoskeletal complaints. Future researches may explore other factors influencing musculoskeletal disorders or employ different research methods. Keywords: ergonomic attitudes, musculoskeletal disorders, nursing profession students